2012
DOI: 10.5572/ajae.2012.6.2.118
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aircraft Traffic Emissions on the Soil Surface Contamination Analysis around the International Airport in Delhi, India

Abstract: To investigate the effect of aircraft traffic emissions on soil pollution, metal levels were analyzed for 8 metals (Fe, Cr, Pb, Zn, Cu, Ni, Mn and Cd) from the vicinity of the Indira Gandhi International (IGI) airport in Delhi, India. The texture of the airport soil was observed to be sandy. Among the metals, Cd showed minimum concentration (2.07 μg g -1 ), while Fe showed maximum concentration (4379 μg g -1 ). The highest metal accumulation was observed at the landing site. Significant correlations were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 50 publications
0
10
0
1
Order By: Relevance
“…The acceptable standards for cadmium are exceeded three times to the east and twice to the west of Krakow. The content of copper and lead exceeded the admissible level in deciduous and coniferous stands 35 km (Nichols et al 1981;Ray et al 2012).…”
Section: Discussionmentioning
confidence: 83%
“…The acceptable standards for cadmium are exceeded three times to the east and twice to the west of Krakow. The content of copper and lead exceeded the admissible level in deciduous and coniferous stands 35 km (Nichols et al 1981;Ray et al 2012).…”
Section: Discussionmentioning
confidence: 83%
“…Other elements (Cu, Cr, Ni, and Zn) were then associated with natural sources in that study. In the similar research on the effect of aircraft traffic emission on soil pollution, Ray et al [23] designated air transport as a possible emitter of Cu, Pb, Zn, Cr, and Ni causing soil contamination, especially by Cd and Pb. Likewise, Massas et al [16] linked air traffic with possible emissions of Cu, Pb, Zn, and, to a limited extent, Ni.…”
Section: Resultsmentioning
confidence: 99%
“…Ray et al [22] also stated, that since Cu, Pb, and Zn are used as additives to aviation fuels, they can be released in these emissions. Rao et al [23] reported their importance to soil contamination at airports. Less explored is the difference between take-off and landing in these emissions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cadmium (Cd) has drawn most environmental concern with respect to significant ecological risk due to high toxicity and mobility (Bi et al, 2006;Kim et al, 2003Kim et al, , 2009Ma et al, 2012;Ray et al, 2012). The US EPA (2011) has classified airborne cadmium as a probable human carcinogen (Group B1) listed substance (with limited evidence of carcinogenicity).…”
Section: Introductionmentioning
confidence: 99%